Efficacy of drainage blood reinfusion in early postoperative period after total hip arthroplasty in patients with rheumatoid arthritis - N B Shelokova; E P Koshurnikova; E V Roznev; M D Zubova; E V Arshin (Научно-практическая ревматология, 2008)
To study effect of drainage blood reinfusion in early postoperative period (EPP) after total hip arthroplasty (THA) in patients with rheumatoid arthritis (RA). Material and methods. Primary THA was performed in 51 RA pts with hip damage (49 female, 2 male aged from 26 to 68 years). 42 THA were performed with “Endosystems and Implants” (ESI) endoprosthesis, and 21 — with “Mathys” endoprosthesis. The pts were divided into two groups. Standard infusion-transfusion therapy with donor blood components was performed in group 1 pts (n=26) to compensate blood loss in EPP. In group 2 pts (n=25) drainage blood reinfusion was done with active aspiration system Handy Vac TM ATS (Unomedical). Group 1 pts had more prominent circulatory and neurologic disturbances in EPP: hypodynamic variant of circulation with elevation of peripheral vascular resistance till 5-7 day of postoperative period, prominent hypersympathicotonia and a large number of posttransfusion reactions. Evaluation of hemodynamic and vegetative disturbances showed advantage of blood loss compensation and vegetative disturbances normalization with drainage blood reinfusion in EPP after THA in comparison with standard pts management.